Некоторые результаты кольцевания летучих мышей в Горном Крыму - Волох, Анатолий Михайлович; Волох, Анатолій Михайлович; Volokh, Anatolii; Кармышев, Ю. В. (My University, 2001)
RU: Приведена информация о результатах кольцевания и численности летучих мышей в пещерах Горного Крыма во время их зимовки 1982-1990 гг. Сообщено об оседлости большого и малого подковоносов, а также подчеркнута необходимость продолжения работ по кольцеванию рукокрылых и мониторинга популяций. EN: Information about the results of bat ringing is given and their numbers wintering in the Crimea caves in 1982—1990 are presented. The settled way of life in the lesser and the greater horseshoe bats is discussed. The necessity of the continuation of bat ringing and population monitoring is shown.
Some Results of Bat Ringing in the Crimean Mountains
Keywords: кольцо; пещера; рукокрылые; спелеологи; ring; cave; bats; speleologists